FEMALE LABOR WORKING INTENSITY: A STUDY CASE IN A CONSTRUCTION JOB - Agus Suseno; Abdul Hakim (Benefit: Jurnal Manajemen dan Bisnis, 2014)
This paper analyzes demographic and socio-economic characteristics of female labor in Bantul District. The characteristics are measured by their education, ages, marital status, number of children, house location, distance from workplace, and salary. The contribution of female labor to their families are analyzed by arithmetic mean. To model the behaviour of female labor work intensity, this paper uses salary, number of children, distance to work location, husband income, and dummy variables on free rice program, health insurance program, and house location. Using a multiple regression model, it finds that variables significantly increase work intensity are salary and husband’s income, while those significantly decreases work intensity are number of children, distance to workplace, and rice free program.